KANDUNGAN LOGAM Cu DAN Pb DALAM TANAMAN BAYAM DAN BIOAVAILABILITASNYA DALAM TANAH PERTANIAN DENGAN PEMBERIAN PUPUK KANDANG SAPI - Siaka, I M.; Arimbawa, I W. B.; Sudiarta, I W. (Jurnal Kimia (Journal of Chemistry); Vol. 15, No.1, Januari 2021, 2021)
Contamination of heavy metals on agricultural soil can have an impact on the quality of agricultural crops. This study aimed to determine the effect of the addition of cow manure on the bioavailability of heavy metals, Cu and Pb in agricultural soil and the content of those metals in spinach plants produced from the soil. The metals contents were obtained through the sequential extraction and wet digestion methods, followed by the measurement of metal concentration using an AAS tool (Shimadzu A 7000). In this study, it was found that the metal content of Cu and Pb in spinach plants whose soil was given fertilizer of cow manure was lower than that of the soil without fertilizer. The average content of Cu and Pb in all parts of the spinach plant without fertilizer application was 53.5985 ± 0.3943 and 59.7982 ± 2.8389 mg/kg, while those given the fertilizer were 41.7626 ± 1.3590 and 52.4335 ± 0.8434 mg/kg, respectively. The level of Cu and Pb bioavailabilities also decreased with the addition of the fertilizer. The number of Cu and Pb metals being bioavailable have decreased, while the metals which were potentially bioavailable have increased significantly. Therefore, the application of cow manure as fertilizer to the agricultural soil could reduce the bioavailability of Cu and Pb metals, and their accumulation in spinach plants, as well.